PHARMACOKINETIC OF CHLORAMPHENICOL IN CALVES INFECTED EXPERIMENTALLY WITH SALMONELLA TYPHIMERIUM - Aziz Alkhayat, Ali; Gazi Habasha, Faisal; Michae, Khalid (The Iraqi Journal of Veterinary Medicine, 1989)
The pharmacokinetic of chloramphenicol was studied in 8 calves .These calves were infected experimentally with Samonella typhimorium The drug was injected intramuscularly at a dose of 50 mg/kg b.w. every 12 hours for a total of 7 injections. The treatment started 48 hours after the appearance of the clinical symptomes (fever, diaheria and dehydration). Blood samples were taken at regular intervals after the 1st and 7th injection and at 12 hour intervals during treatment. Plasma disappearance curves were constructed by which the biological half lives (t1/2s) and volume of distribution (vds) were calculated. Peak plasma concentrations were 22.57 and 46.46 ug/ml after the 1st and 7th injection respectively. Both occured 3 hours after injection. The concentrations after 12 hours ranged from 5.9 to 21.6 ug/ml. The t 1/2 s were 4.34 and 8.73 hrs and the values of (vd) were 1.4 and 0.8 1/kg after the 1st and 7th injection respectively.